Peningkatan Sains dan Kreativitas Masyarakat Melalui Budidaya Bawang Dayak Secara Organik dan Pengolahan Kompos Limbah Pasar Tradisional - Titin Apung Atikah; Muliansyah Muliansyah; Astri Widiarti; Pienyani Rosawanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Today, the tendency of people to return to life to return to nature with the belief that taking natural medicines is relatively safer than synthetic drugs has an impact on the high demand for natural medicines. Dayak onion (Eleutherine palmifolia Merr.) is one of the typical types of medicinal plants in Kalimantan wherein its use as a medicinal plant the tubers are consumed in the form of freshly boiled water or in the form of simplicia. Activities with training methods and demonstrations/practices are one of the solutions that can be done. The results of community service activities showed that all participants participated actively and could receive all the knowledge and skills transferred by the PKW team and were interested in doing it themselves at home where organic crop products would be consumed by themselves (40% ) and sold (60%) with processed food and beverage products (55%) and traditional forms of medicine (45%). Likewise, for the processing of compost made from traditional market waste, compost processed products will be used alone (85%) and sold (15%) with compost products made from market waste (80%) and other compost made from ingredients (20%) of interest. The data shows that the Community Service Program conducted by the University of Palangka Raya can contribute and be a solution to overcome the problems faced by partners